Effects of 6-[p-(4-Phenylacetylpiperazin-l-yl)-phenyl]-4,5-Dihydro-3(2H)-Pyridazinone (CCI 17810) and Aspirin on Experimental Arterial Thrombosis in Rats - Lecker, Dorothy; Kumar, Abhilash (Thrombosis and Haemostasis, 1980)
An experimental model for arterial thrombosis has been investigated in rats. A loop of polythene tubing inserted in the left carotid artery induced thrombus formation on the arterial wall at the points of contact with the tips of the cannula. Sprague Dawley (CFY) rats were more susceptible to the thrombotic stimulus than were Wistar (WAG) rats. Whole blood platelet adhesiveness measured by a glass bead column method was higher in CFY rats than in WAG rats.6 - [p - (4-Phenylacetylpiperazin-1 - yl) - phenyl] - 4,5 - dihydro-3(2H)-pyridazinone (CCI 17810) inhibited thrombus formation in CFY rats. Both the incidence of occlusion of the cannulated artery and the mean thrombus weight were reduced by CCI 17810 in doses of 25, 50 or 100 mg/kg administered orally twice daily; the effects were dose-related.The effects of aspirin depended on the dose administered. A high dose (200 mg/kg) did not inhibit thrombus formation whereas a low dose (20 mg/kg) reduced the incidence of occlusion and the mean thrombus weight. These results are in accord with the differential effects of aspirin on platelet and blood vessel wall cyclooxygenase.
Keywords: Pyridazinone derivative